Pengaruh Kualitas Produk Dan Promosi Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Pada Konsumen Maybelline Di Semarang) - Olivia, Gegahertzy Rindo; Ngatno, Ngatno (Universitas Diponegoro, 2021)
Abstract: Along with the times, cosmetics seem to be a primary need for some women. Cosmetics are one of the most important needs for a woman. Therefore, many cosmetic companies are competing to meet customer needs by issuing product innovations. Product quality is an important factor that influences customer satisfaction creation. Product quality is a determining factor for customer satisfaction after purchasing and using a product. Maybelline's success in getting customers cannot be separated from the role of product promotion. Promotions offered are very influential on customer satisfaction, by means of marketing that are done must be able to attract every existing customer by implementing a good marketing strategy. Customer loyalty has an important role in a company, maintaining them means increasing financial performance and maintaining the survival of the company. Therefore, product quality, promotion, customer satisfaction and customer loyalty can be suspected to be the factors that cause fluctuations in Maybelline. The results showed that partially product quality contributed 60.2% of customer satisfaction, 54.5% variable customer satisfaction was influenced by promotional variables, 71.9% variable product quality and promotion influenced customer satisfaction variables, as much as 47.7% loyalty. Customers are influenced by product quality, as much as 68.7% of the promotional variables affect the customer loyalty variable, and as much as 61% of the customer loyalty variable is influenced by the customer satisfaction variable. Based on the research results, it is recommended that Maybelline employees be more informative to customers so that customers will feel attracted to Maybelline products. Besides that, Maybelline can also make a product innovation so that customers are more interested in buying Maybelline products. Keywords: Product Quality; Promotion; Customer Loyalty; and Customer Satisfaction. Abstrak:. Kualitas produk, menjadi faktor penting yang berpengaruh dalam penciptaan kepuasan pelanggan. Kualitas produk merupakan faktor penentu kepuasan pelanggan setelah melakukan pembelian dan pemakaian terhadap suatu produk. Kesuksesan Maybelline mendapatkan pelanggan tidak lepas dari peran promosi produk. Promosi yang ditawarkan sangat berpengaruh terhadap kepuasan pelanggan, dengan cara-cara pemasaran yang dilakukan harus dapat menarik setiap konsumen yang ada dengan melakukan strategi pemasaran yang baik. Loyalitas pelanggan memiliki peranan penting dalam sebuah perusahaan, mempertahankan mereka berarti meningkatkan kinerja keuangan dan mempertahankan kelangsungan hidup perusahaan. Maka dari itu, kualitas produk, promosi, kepuasan pelanggan dan loyalitas pelanggan dapat diduga menjadi factor penyebab fluktuasi pada Maybelline. Hasil penelitian menunjukan bahwa secara parsial kualitas produk menyumbang sebesar 60,2% dari kepuasan pelanggan, 54,5% variabel kepuasan pelanggan dipengaruhi oleh variabel promosi, 71,9% variabel kualitas produk dan promosi mempengaruhi variabel kepuasan pelanggan, sebanyak 47,7% loyalitas pelanggan dipengaruhi oleh kualitas produk, sebanyak 68,7% variable promosi mempengaruhi variable loyalitas pelanggan, dan sebanyak 61% variable loyalitas pelanggan dipengaruhi variabel kepuasan pelanggan. Berdasarkan hasil penelitian, maka disarankan supaya pegawai Maybelline lebih informative kepada pelanggan sehingga pelanggan akan merasa tertarik kepada produk Maybelline. Selain itu Maybelline juga dapat membuat suatu inovasi produk agar pelanggan lebih tertarik untuk membeli produk Maybelline. Kata Kunci : Kualitas Produk; Promosi; Loyalitas Pelanggan; dan Kepuasan Pelanggan